Imaging of tumours of the urinary tract in children, with particular reference to Wilms' tumour - Cremin, Bryan J (Department of Paediatrics and Child Health, 2018)
The investigation of an abdominal mass in a child is a common problem in the radiology department of the Red Cross Children's Hospital. The majority of these masses involve the urinary tract. The commonest neoplasm is a Wilms' tumour of the kidney. Against a pathological and clinical background, the investigation of Wilms' tumour by diagnostic imaging is presented. The imaging modalities currently utilised are the intravenous urogram (IVU), ultrasound (US), computed tomography (CT) and magnetic resonance (MR). Using the material available in the last decade, the principles, techniques and imaging characteristics of these modalities are investigated and compared. These results are reflected against those reported in the medical literature. This literature is not yet extensive as the current technology has only been available for the last six to seven years. The IVU has in the past been the main imaging modality and we still use it extensively. Its strengths and weaknesses are discussed. In the last five years US has taken its place as the primary method of diagnostic imaging. We have found that with our increasing experience that this is justified. The use of US and IVU in a practiced hand is a powerful diagnostic combination. CT as a primary investigation is not readily available at our institution. We have used it for comparative purposes in about 20% of our recent cases. CT has not added greatly to our initial diagnostic impression. However, it has been most useful for follow up of metastasis and for assessing the normality of the lungs before ceasing chemotherapy. Our experience with MRI is limited and confined to unusual presentations in the last year. Other modalities such as arteriography and nuclear medicine have special indications which are to be discussed. The remaining tumours of the upper urinary tracts are all rare, but are reported and the literature researched. In the lower urinary tract the main pelvic lesion is a rhabdomyosarcoma. The comparative advantages of the IVU, US, CT and MRI are also noted. In the pelvis, US has also become the primary imaging modality, and is replacing contrast medium cystography. However, examples of the latter are included as it still has a place, particularly in the less sophisticated institutes. CT and MRI, when available, have imaging advantages in the pelvis and are becoming the methods of choice for follow up. The main objective of this document has been to investigate the available imaging techniques, but, against this overall theme, the clinical care of the child is most important. With this in mind the treatment protocols that are used at our hospital are noted in the appendices to the thesis.